Perceived organizational climate, job satisfaction and job performance among professional and support group of Bank Pertanian Malaysia in Sabah - Cagampang, Victor (1998)
This study was conducted to determine and explore BPM's professional and support group perceptions on the Organizational Climate 10 relation to Job Satisfaction and Job Performance A total of 166 respondents consIst1Og of branch managers, credit and finance officers, and the clerical staff were selected by us10g the cluster sampling method The study used self-administered structured questionnaire encompassing the Organizational Climate instrument. Job Satisfaction Survey and Job Performance 10struments Factor analysis of climate Items Yield 10 dimensions, namely risk, identify and affective tone toward people, rewards, individual autonomy, accountability, rules on orientation, individual performance standards, individual commitment, organizational role, organizational autonomy and organizational standards Perceived organizational climate shows contentment with the derived climate constructs mentioned above, except on rewards and an item on 'loyalty to the bank' Whereas, perceived Job Satisfaction shows concern on the facet of pay, promotion, fringe benefits, contingent rewards and operating conditions but shown contentment on the supervision, communication, coworkers and nature of work Perceived Job Performance indicate moderately high above 43%.